Foundations for practise in occupational theraphy - Duncan, Edward A. S. (Churchill Livingstone/Elsevier, 2012)
A practical reference tool which is both a guide to undergraduates and a practical reference tool for clinicians in the application of models and theories to practice. Underlining the importance and clinical relevance of theory to practice, this text provides an excellent introduction to the theoretical basis of occupational therapy. Contributions are given by both academics and expert clinicians.